Dynamic Ethernet Link Shutdown for Energy Conservation on Ethernet Links - Gupta, M.; Singh, S. (2007 IEEE International Conference on Communications, 2007)
Recent studies of network traffic utilization on campus networks have shown that data networks remain heavily under-utilized. Yet currently there is little attempt to save energy on network interfaces by using the low power modes available in Ethernet transceivers during periods of inactivity or low utilization. In this paper we design and evaluate a dynamic ethernet link shutdown (DELS) algorithm that utilizes current technology leading to significant benefits in energy savings with little noticeable impact on packet loss or delay. The algorithm uses buffer occupancy, the behavior of previous packet arrival times and a configurable maximum bounded delay to make sleeping decisions. The scheme was evaluated using simulations with inputs generated using a synthetic traffic generator for smooth and bursty traffic. The results show that the percentage of total time that a link can be shut down can be anywhere from 80% to 60% for traffic loads up to 5%.